TRANSLITERASl DAN ANALISIS AJARAN MORAL TEKS SAIR SRI PADOEKA TOEAN BESAR BERANGKAT BELAJAR KARYA MOHD HASJIM DALAM NASKAH SJAIRS - Idayanti, Iik (Universitas Lancang Kuning, 2016)
A manuscript entitles Sairs which becomes the object of this study is a manuscript written in Arabic-Malay script. This text consists of three texts, one of the texts that becomes the object o this study is Sair Slamat Sri Padoeka Tbean Besar Berangkat Belajar written by Mohd Hasjim in Riau on March 30, 1896. The text contains moral advice. The text content is important to be dug to bring up what it implies, therefore, it is necessary to do the transliteration of the Arabic script to Syairs, Sair Slamat Sri Padoeka Toean Besar Berangkat Belajar in order it can be read by public and it can be analyzed as well. The text contains some moral values dealing with humans relation to themselves, their relation to other humam beings as well as to God.